2010
DOI: 10.1002/pssa.201026046
|View full text |Cite
|
Sign up to set email alerts
|

(In)AlGaN deep ultraviolet light emitting diodes with optimized quantum well width

Abstract: The effect of the quantum well (QW) width on the light output and efficiency of ultraviolet (UV) light emitting diodes (LEDs) has been investigated. The carrier injection in the devices is simulated and compared with electroluminescence (EL) measurements. The light output power depends clearly on the QW thickness. The highest output power has been found for the LEDs with a QW thickness of 2.2 nm. This effect is attributed to the trade-off between electron and hole wave function overlap and carrier concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Nakahara et al focused on the transparent (or reflective) electrode in the UV region. Hirayama et al and Kolbe et al reported that varying the carrier confinement structures and characteristics, such as multi‐quantum‐barrier electron‐blocking layers (EBL) or QW thickness, could increase the efficiency of UV LEDs. However, despite these efforts, the AlGaN‐based UV LED efficiency remains low and must be further improved to enable their use in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nakahara et al focused on the transparent (or reflective) electrode in the UV region. Hirayama et al and Kolbe et al reported that varying the carrier confinement structures and characteristics, such as multi‐quantum‐barrier electron‐blocking layers (EBL) or QW thickness, could increase the efficiency of UV LEDs. However, despite these efforts, the AlGaN‐based UV LED efficiency remains low and must be further improved to enable their use in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the EBL is critical to prevent electron leakage from the quantum well active region into the p-doped layers of the LED and to provide efficient hole injection into the active region. [4][5][6] EBLs for UV-B and UV-C LEDs require p-doped Al x Ga 1Àx N layers with a typical thickness of around 20 nm and an aluminum content x of more than 75%. [7][8][9] Because of the very high activation energy of the magnesium acceptors in such high aluminum mole fraction layers, 10,11 it is very challenging to realize conductive p-doped AlGaN:Mg EBLs.…”
mentioning
confidence: 99%
“…One promising area of efficiency improvement is to increase the radiative recombination rates in the active region. Therefore, we have previously discussed the influence of the quantum‐well (QW) and quantum‐barrier composition (), the QW numbers () and the QW width () on the emission characteristics of UV LEDs. The second key challenge to realize efficient UV LEDs is an efficient carrier injection and a good carrier confinement.…”
Section: Introductionmentioning
confidence: 99%